Menakar Pengaruh dari Ambidextrous Leadership terhadap Business Agility dari Perusahaan Publik di Masa Krisis - Nopriadi Saputra (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This article attempts to explore ambidextrous leadership and its effects on business agility and firm performance. Is it relevant to tend to explorative, exploitative, or balanced in leading a company in crisis conditions? How does ambidextrous leadership impact on business agility in supply chain, operations, and marketing function? This article is based on a cross-sectional study which collecting perceptual responses from 113 senior management from 34 public listed companies on Indonesia Stock Exchange (IDX). Data was collected by online-questionnaire with convenience approach. The data was then analyzed with SmartPLS version 3.3.9. The results reveal to be explorative rather than exploitative for being more agile in doing business. Supply chain agility is the most influential function for being agile in business rather than operational or marketing agility in generating firm performance.